DIAMETER MEASUREMENTS OF A 700-M DEEP BORE-HOLE AT MIZUHO STATION, EAST ANTARCTICA - オクヒラ, フミオ; ナルセ, レンジ; ナカオ, マサヨシ; カワダ, クニオ; OKUHIRA, Fumio; NARUSE, Renji; NAKAWO, Masayoshi; KAWADA, Kunio (National Institute of Polar Research, 1987)
P(論文) The closure rate was obtained by measuring the change in diameter of the bore-hole. The diameter measurements were firstly made on 3rd August 1984,the second day after the completion of the drilling. It was repeated eighttimes for one year and a half, and the last measurements were carried out on 19th January 1986. The strain rate of the bore-hole was calculated from these observations. It decreased with time at shallow depths continuously, indicating that the steady state had not been reached for the observation period. At deeper depths, the strain rate decreased in the early period, but icreased at later stages, taking a minimum value in between. The minimum strain rate was achieved earlier at deep depths than at shallow depths. A power law was obtained between the minimum strain rate and the shear stress at various depths. The power law was compatible with that derived from observations of surface flow at Mizuho Plateau. departmental bulletin paper